Sexual dimorphism of the human mandible and its association with dental development. - Coquerelle, Michael; Bookstein, Fred L; Braga, José; Halazonetis, Demetrios J; Weber, Gerhard W; Mitteroecker, Philipp (Am J Phys Anthropol, 2011)
The present study investigates whether the human mandible is sexually dimorphic during early postnatal development and whether early dimorphic features persist during subsequent ontogeny. We also examine whether mandibular dimorphism is linked to dimorphism of dental development. Dense CT-derived mandibular meshes of 84 females and 75 males, ranging from birth to adulthood, were analyzed using geometric morphometric methods. On the basis of the specimen's chronological ages and mineralization stages of the deciduous and permanent teeth, we compute dental age as proxy for dental development by the additive conjoint measurement method. By birth, males have, on average, more advanced age-specific shapes than females. However, sex differences decrease quickly as females catch up via a different association between shape and size. This leads to an almost complete reduction of sexual dimorphism between the ages of 4 and 14. From puberty to adulthood, males are characterized by allometric shape changes while the shape of the female mandible continues to change even after size has ceased to increase. Dimorphism of dental maturation becomes visible only at puberty. Sexual dimorphism, concentrated at the ramus and the mental region during the earliest ontogenetic stages and again at adulthood, is not associated with the development of the teeth. At puberty there is a simultaneous peak in size increase, shape development, and dental maturation likely controlled by the surge of sex hormones with a dimorphic onset age. We argue that the infant and adult dimorphism of the mental region may be associated with the development of supralaryngeal structures.
Keywords: Adolescent; Child; Child, Preschool; Dentition; Female; Humans; Infant; Male; Mandible; principal component analysis; Sex Characteristics; Tomography, X-Ray Computed; Tooth; Young Adult